1996
DOI: 10.1007/s004390050108
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the neurofibromatosis type 2 gene in different human tumors of neuroectodermal origin

Abstract: The autosomal dominant syndrome neurofibromatosis type 2 (NF2) is characterized by the development of bilateral vestibular schwannomas, meningiomas, ependymomas and gliomas. The NF2 gene, recently isolated from chromosome 22, is mutated in both sporadic and NF2 tumors such as schwannomas, meningiomas and ependymomas. Mutations of the gene have been described not only in the neoplasms usually associated with NF2, but also in 30% of the melanomas and 41 % of the mesotheliomas analyzed. In particular, the finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Considering what is known to date about the NF2 gene mutational spectrum in different tumors, it can be assumed that at least two of the latter three mutations (M46 – aberrant splicing and M115 – nonsense mutation) are pathogenic. These types of mutations are, however, usually combined with the second inactivating hit on the remaining normal allele of the gene [13,44-47]. The third aberration is a missense mutation (tumor M87, exon 4, 436 G>A, Val-146-Ile, Table 1), which is possibly introducing a dysfunction to the N-terminal FERM domain (residues 1–302 of the protein, plasma membrane binding domain) of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…Considering what is known to date about the NF2 gene mutational spectrum in different tumors, it can be assumed that at least two of the latter three mutations (M46 – aberrant splicing and M115 – nonsense mutation) are pathogenic. These types of mutations are, however, usually combined with the second inactivating hit on the remaining normal allele of the gene [13,44-47]. The third aberration is a missense mutation (tumor M87, exon 4, 436 G>A, Val-146-Ile, Table 1), which is possibly introducing a dysfunction to the N-terminal FERM domain (residues 1–302 of the protein, plasma membrane binding domain) of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been found that NF2 is mutated in most meningiomas and schwannomas (Lekanne Deprez et al, 1994;Merel et al, 1995;Papi et al, 1995;Slavc et al, 1995;De Vitis et al, 1996), some cases lacked expression of the NF2 protein without biallelic NF2 inactivation (Stemmer-Rachamimov et al, 1997). Kimura et al (2000) demonstrated that, in some of these cases, post-translational regulation of merlin through a calpain-mediated proteolysis pathway may be responsible for the absence of NF2 protein.…”
Section: Discussionmentioning
confidence: 97%
“…46 Modern molecular techniques have demonstrated that the mutation was not only found in meningiomas in patients with NF-2, but also in the majority of patients with sporadic meningiomas. [47][48][49][50][51][52] Most mutations occur in tumors that have already lost one chromosome 22 allele, supporting the ''two-hit'' hypothesis for tumorigenesis ( Fig. 1).…”
Section: Chromosonal Abnormalities and Tumor Suppressor Genesmentioning
confidence: 59%